Desa Wisata : Integrasi Pengelolaan Berbasis Kearifan Lokal Dan Manajemen Kontemporer - Ahmad Subhan Mahardani (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This article aims to explain the phenomenon of managing a tourist village which has its own characteristics compared to the mainstream management practices commonly found in the corporate/private sector. Explanation of the phenomenon of managing tourism villages is carried out through studies using in-depth literature review techniques. The characteristics of the management of the Tourism Village are based on the local cultural background and the local wisdom that is owned and the orientation of the Tourism Village itself which is categorized as social business or social entrepreneurship. In the results of the studies that have been carried out, in essence management in the context of management based on local wisdom and contemporary management practices commonly found in corporations/private sectors can be adopted in the management of Tourism Villages with a number of adjustments, so that they remain relevant. Keywords : Tourist Village, Local Wisdom, Contemporary Management